EXPERIMENTAL STUDY ON ADDING POLYPROPYLENE FIBER TO COMPRESSIVE STRENGTH AND FLEXURAL STRENGTH OF CONCRETE - Sumarno, Agung; Syafwandi; Kevin Deodatus, leonardus (Neutron, 2020)
Concrete is one of the most frequently used materials in the construction world, concrete is generally composed of a mixture of fine aggregate composition. Coarse aggregate, water and cement. However, concrete has a weakness to the ability to withstand the flexural force, today concrete has experienced a lot of innovations, one of which is fiber concrete. Polypropylene fiber is a type of fiber that can be used as an added material in concrete. This research was conducted to determine the effect of adding polypropylene fiber on compressive strength and flexural strength of concrete. Tests in this study were carried out according to SNI (Indonesian national standard) and ASTM (American standard testing and material), from the results of the experiment of adding polypropylene fiber with variations of 0%, 1%, 1.2%, and 1.4% known to have an effect to the compressive strength and flexural strength of concrete. The highest compressive strength and flexure obtained in concrete variations of 1%. By using cylindrical and beam test specimens.